The Effect of Work Discipline and Compen station on the Performance of Teacher and Staff at the Pelita Medan Foundation in 2021 - Sinaga, Sahat; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
This study includes the influence of two independent variables, namely work discipline and compensation obtained by teachers and staff at the Pelita Medan Foundation in 2021. This research is a quantitative study using a survey method, in which basic data from a sample of a population is collected using a questionnaire instrument in field. The data used in this study is primary data. Primary data is obtained directly from the original source through the distribution of questionnaires to respondents. The research population is all teachers and staff at the Pelita Medan foundation as many as 40 people with the number of samples used as total sampling. Data collection techniques were carried out by interviewing and distributing questionnaires to respondents. Classical assumption test is done by normality test, multicollinearity test, heteroscedasticity test. The data analysis technique used the T test and F test. The results showed that the t value of work discipline > t table, namely the t value of work discipline was 2,277 > 1,686, as well as the t value of compensation > t table, the t value of compensation was 2,510 > 1,686. This shows that there is a positive and significant effect between work discipline and compensation on the performance of teachers and staff. Meanwhile, it simultaneously shows that the calculated F value > F table (5.286 > 3.25) thus the regression model between work discipline and compensation on teacher performance is declared fit or good.